High Protein Intake and Likely Association with Non-Insulin Dependent Diabetes Mellitus (NIDDM) - Bonsi, E.A.; Chibuzo, E.C. (Pakistan Journal of Nutrition, 2014)
Epidemiologic studies have demonstrated an association between Diabetes and macronutrients. An increase in the incidence of Diabetes prompted this investigation into the relationship between the dietary energy and of macro-nutrients intake and diabetes. A cross sectional, nested case-control study was conducted to examine the association of risk for NIDDM with energy and macro-nutrients consumption. One hundred subjects aged 40-82 years, stratified into diabetic cases and controls using fasting and 2 h post prandial Plasma Glucose levels constituted the sample size. The risk for Diabetes was measured using Pearson Correlation (r) and Odds Ratio (OR) with Epi info version 5. A 24-hour dietary recall generated quantitative estimates of their energy and macronutrients consumption. The results showed that percent protein (PP) energy significantly correlated with type 2 diabetes mellitus (r = 0.20, p15.5% gave an OR = 1.19 (CI = 0.27-4.76) and was a risk factor for type 2 diabetes mellitus. A PP of 15.5% was a risk factor for type 2 diabetes.